Employee Work Motivation In Maintaining The Performance Of Balikpapan Regional Hospital Nurses During The Covid-19 Pandemic - Didik Hadiyatno; Tutik Yuliani; Pudjiati Pudjiati (Eduvest - Journal of Universal Studies, 2021)
This study aims to analyze the effect of Motivation, Work Environment, and Compensation Variables on the Performance of Nurses at Regional Hospitals in Balikpapan, both Simultaneously and Partially. The population is 138 people with sample j used is 138 nurses and the analysis tool used is multiple linear regression. From the results of the simultaneous test, it was obtained that there was a strong relationship between the variables of Motivation, Work Environment and Compensation on the Nurse Performance variable at the Hospital in Balikpapan. it can be concluded that the variables of Motivation, Work Environment and Compensation are proven together to have a significant effect on the variable of Nurse Performance at Hospitals in Balikpapan. Meanwhile, based on the results of the partial test, it was found that the variables of motivation, work environment, and compensation proved to have an influence on the performance of nurses at the Balikpapan Regional Hospital, that it was the compensation variable that had a dominant influence on the performance of hospital nurses in Balikpapan.